ANALYSIS OF SELF-SERVICE BOXES IN PARDUBICE : PARCEL LOCKERS IN PARDUBICE (Perner's Contacts, 2022)
The paper deals with the issue of last-mile delivery. Last-mile delivery is one of the main factors affecting the number of commercial vehicles moving around the city. Because of the steady increase in e-commerce, which is primarily focused on home delivery. In recent years, the use of self-service boxes as an effective last-mile delivery system has been applied as a very interesting solution to reduce the number of vehicles in cities. This article focuses on the analysis of the current state of self-service boxes and the possibilities of their use in Pardubice.
Keywords: parcel lockers; e-commerce; last-mile delivery